Breast-feeding protects against respiratory syncytial virus infections. Issue 6030 (31st July 1976) - Downham, M A; Scott, R; Sims, D G; Webb, J K; Gardner, P S
Abstract : Eight out of 115 infants admitted to hospital with respiratory syncytial (RS) virus infection had been breast-fed compared with 46 out of 167 controls; this difference was statistically significant. Twenty-one specimens of human colostrum were examined, and all contained RS virus neutralising activity. Specific IgA and IgG were detected in 18 specimens, whereas IgM was detected in none. The titre of IgA antibody was usually higher and correlated more closely to the titre of neutralising activity than that of IgG. Infants inhale milk feeds and regurgitate them through the nose, and the IgA collecting in the respiratory tract might protect against severe respiratory infection. Alternatively, if severe RS virus illness is a sign of hypersensitivity to the virus breast-feeding might protect the infant from an early sensitising infection.